Substation Monitoring System - Muntode, Handal Shukracharya; Muntode, Ovhal Shubham; Muntode, Idhate Sushama; Muntode, Kothawale Ashutosh; Muntode, Dr. Avchat H. S (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The work named ‘Substation Monitoring System’ proposes an innovative design to develop a system based on microcontroller. It is used for monitoring the voltage, current and temperature of a distribution transformer in a substation and to protect the system from the rise in mentioned parameters. The objective is to monitor the electrical parameters continuously and hence to guard the burning of distribution transformer due to the constraints such as overload, over temperature and input high voltage. If any of these values increase beyond the limit then the entire unit is shut down by operating an Electromagnetic Relay. This relay is activated as soon as the parameters exceed the predefined threshold values. The relay also works as a circuit breaker to switch off the main power supply. RF communication is used to continuously send the instantaneous values to the intermediate station. The GSM modem is used to send the real time electrical parameters in the form of SMS. The system is designed to send a SMS alerts to the authorized person whenever the parameters (Voltage, Current and Temperature) exceeds the predefined limits. Supplying electricity to consumers necessitates power generation, transmission, and distribution. Initially electric power is generated by using electric generators such as: nuclear power generators, thermal power generators and hydra ulic power generators and then transmitted through transmission systems using high voltage. Power departs from the generator and enters into a transmission substation, where huge transformers convert the generator’s voltage to extremely high voltages (155kV to 765 kV) for long-distance (up to about 300 miles) transmission . Then, the voltage level is reduced using transformers and power is transferred to customers through electric power distribution systems. Power starts from the transmission grid at distribution substations where the voltage is stepped-down (typically to less than 10kV) and carried by smaller distribution lines to supply commercial, residential, and industrial users . Monitoring and controlling of substations is an important task for supplying healthy power to the consumers in this automated era. But due to the aging infrastructure of the distribution grids (substations) and lack of automation systems that monitors the critical conditions at the substations, the risk of blackouts, brownouts and fire are rapidly increasing. Substations consist of different electronic components like transformers, circuit breakers, relays etc. The transformer fluid leaks or internal insulation breakdown cause overheating that leads to failures. The traditional method includes periodic manual checking of the system which is time consuming and with very low accuracy Power departs from the generator and enters into a transmission substation, where huge transformers convert the generator’s voltage to extremely high voltages (155kV to 765 kV) for long-distance (up to about 300 miles) transmission . Then, the voltage level is reduced using transformers and power is transferred to customers through electric power distribution systems. Power starts from the transmission grid at distribution substations where the voltage is stepped-down (typically to less than 10kV) and carried by smaller distribution lines to supply commercial, residential, and industrial users . Monitoring and controlling of substations is an important task for supplying healthy power to the consumers in this automated era. But due to the aging infrastructure of the distribution grids (substations) and lack of automation systems that monitors the critical conditions at the substations, the risk of blackouts, brownouts and fire are rapidly increasing. Substations consist of different electronic components like transformers, circuit breakers, relays etc. The transformer fluid leaks or internal insulation breakdown cause overheating that leads to failures